COMMUNITY CAPACITY FOR QUALITY STANDARDIZATION OF LIQUID FERTILIZER BASED ON LOCAL DAIRY COW MANURE POTENTIAL IN BRAU-BATU - Muhammad Ikhlas Abdjan; Maria Monica Sianita; Pirim Setiarso; Nur Hayati; Samik; Mirwa Adiprahara Anggarani; Fani Deapsari (Universitas Airlangga, 2026)
A training activity on liquid fertilizer quality standardization based on the potential of dairy cow manure was conducted in the Brau region of ​​Gunungsari Village, Batu City, it initiative aims to increase community capacity in producing liquid fertilizer that meets national quality standards. The program uses a participatory approach that involves livestock farmers and community groups in identifying needs, providing training, conducting quality testing, and providing support for the production process. The training included an introduction to quality parameters according to SNI 4958:2015 and Ministry of Agriculture regulations, a pH measurement demonstration, self-testing practices, and assistance with the production process. Evaluation results showed that participants experienced increased knowledge and skills in independently testing the quality of liquid fertilizer. All participants were able to use measuring instruments correctly and understood basic product standardization procedures. Questionnaire results (n=10) indicated a very positive response to the training and mentoring methods provided, as well as increased participant confidence in implementing quality control on their products. These findings demonstrate that a training approach integrating theory and practice has proven effective in improving community technical literacy and opening opportunities for the development of local liquid fertilizer products that meet quality standards and are ready to enter the formal market.